ESRA19-0361 Gender difference in cancer patients' hesitancy of analgesics use, adherence, and the effectiveness of pain management. (30th August 2019) - Chou, P; Lin, PC
Abstract : Background and aims: Males and females have significant differences in the results from medical outcomes. However, little research has explored the gender differences in cancer patients' perceptions of analgesics, the relationship between gender and analgesic adherence, or the effectiveness of pain management. The aim of this study was to compare gender differences associated with hesitancy to use analgesics, analgesic adherence, or pain management effectiveness. Methods: The study was conducted in the outpatient oncology department of a medical center in Taiwan. A descriptive and cross-sectional design was used. The study samples were collected from 362 cancer patients. The participants completed several measures including the Short Version of the Barriers Questionnaire-Taiwan, the Analgesics Adherence Measure-Taiwan version, the Brief Pain Inventory-Chinese Version, the Pain Management Index, and a demographic and disease questionnaire. Results: The pain intensity was significantly higher among females than among males. The mean S-BQT score for females was significantly higher than that of the males (female=3.38, male=3.19, p<0.01). The PMI results also showed that a larger percentage of the males had adequate pain management. In addition, male gender was a significant predictor of higher analgesic adherence (OR=1.93, p <0.05). Conclusions: Gender could precisely predict the cancer patients' medication adherence. Women experienced significantly greater pain than men, but also had more hesitancy to use analgesics, lower adherence, and inadequate pain management. Medical professionals should consider women a high risk group for inadequate pain control. It is crucial for health providers to consider the gender discrepancy when attempting to improve cancer pain management.